KESIAPAN MENGAJAR MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Hesti Nursuci Rahmadani; Sri Kartikowati; Hardisem Syabrus (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This quantitative study aims to examine students’ preparedness for teaching at the Social Science Education Department, FKIP, Universitas Riau. The research involved 68 active PIPS students selected through simple random sampling from a population of 211 students. Data were collected using a questionnaire distributed via Google Forms and analyzed using descriptive and inferential statistical techniques with SPSS version 24. The results show that teaching motivation was in the very good category (51%), while teaching preparedness was in the very good category (60%). Furthermore, teaching motivation contributed 59% to teaching preparedness, while the remaining 41% was influenced by other factors not examined in this study, such as interest, intellectual capacity, and perception. The analysis also indicated a positive relationship between teaching motivation and preparedness, where an increase of one unit in teaching motivation corresponded to a one-unit increase in teaching preparedness. The study concludes that teaching motivation significantly influences students’ preparedness for teaching as prospective educators.